solve for d
d occurs only in one term, (1/2)*b*c*d. Let's isolate this term moving bc onto the other side of equation.
Formally, subtract bc from both sides:
A - b*c = (1/2)*b*c*d.
Now divide both sides by b*c and obtain
(A - bc)/(b*c) = (1/2)*d, orA/(b*c) - 1 = (1/2)*d.
Finally, multiply by 2 and obtain
d = 2*(A - bc)/bc, ord = 2*A/(b*c) - 2.
(use the form which you consider simpler)
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?